(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Arousal time is variable after sedation with spinal anesthesia after infraumbilical surgeries. Propofol and midazolam have been studied individually using the Observer’s Assessment of Awareness/Sedation (OAA/S) score and different other ways. So this present study was designed to compare the arousal time of sedation for propofol and midazolam using OAA/S scores. Materials and methods: A total of 60 patients were randomly assigned to receive either propofol (Group A, n =30) or midazolam (Group B, n = 30). All patients of Group A received bolus of propofol (1 mg/kg) followed by infusion at 3 mg/kg/h, Group B received bolus of midazolam (0.05 mg/kg), followed by infusion at 0.06 mg/kg/h. OAA/S score was noted at beginning and again during recovery. The time to achieve OAA/S score 5 was noted. Changes of pulse rate, O2 saturation and satisfaction score were noted. Results: Among the 60 patients gender distributions where male and female distributed evenly. Age group distributions revealed more patients were gathered in age group 31- 40 years and >51 years. Regarding physical status most of the patients were at ASA physical status 1. It was found that propofol had better outcome than midazolam in terms of arousal time score and patient’s satisfaction score after surgery. Conclusions: A shorter arousal time from sedation during spinal anaesthesia can be achieved using propofol than arousal time with midazolam. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 18-21